Large Conization and Laparoendoscopic Single-Port Pelvic Lymphadenectomy in Early-Stage Cervical Cancer for Fertility Preservation - Polat Dursun; Mete Caglar; Huseyin Akilli; Ali Ayhan (Case Reports in Surgery)
Fertility preservation in early-stage cervical cancer is a hot topic in gynecologic oncology. Although radical vaginal trachelectomy (RVT) is suggested as a fertility preserving approach, there are some serious concerns like cervical stenosis, second trimester loss, preterm delivery in survivors, and lack of residual tumor in the majority of the surgical specimens. Therefore, less radical surgical operations have been proposed in early-stage cervical carcinomas. On the other hand, single-incision laparoscopic surgery (SILS) is an evolving endoscopic approach for minimal access surgery. In this report, we present a case with early-stage cervical cancer who wishes to preserve fertility. We successfully performed single-port pelvic lymphadenectomy and large conization to preserve fertility potential of the patient. We think that combination of less radical approach like conization and single-port pelvic lymphadenectomy might be less minimally invasive and is still an effective surgical approach in well-selected cases with cervical carcinomas. Incorporation of single-port laparoscopy into the minimally invasive fertility sparing management of the cervical cancer will improve patients outcome with less complications and better cosmesis. Further studies are needed to reach a clear conclusion.